An Analysis of Local Power Structure of Thailand: Evolution and Implications - SATAPORN ROENGTAM (Jurnal Studi Pemerintahan, 2016)
This study presents the results of the investigation about the current characteristics, composition and relationship of actors in the ‘Power Structure of Thailand’. The concept on ‘Power Structure Analysis’ by William Dommhoff is used to construct the conceptual framework and data analysis. The findings are divided into three (3) issues. Firstly, characteristics of the power structure and actors can be divided into three (3) groups, in which all of them have to work together systematically. Secondly, in terms of composition, these groups can be positioned into three (3) rings of power structures: the inner, middle and outer rings. And thirdly, these groups play certain roles according to their relationship. The inner takes responsibility about creating and planning, the middle takes responsibility about command and control, and the outer take responsibility about actions. All of them will have to work together in order to create, use and maintain their power to continuously collect and protect their interests in the province.Keywords: decentralization, local government, local power structure, monetarypower complex